Metabolic rewiring of the hypertensive kidney - Rinschen, Markus Matthias; Palygin, Oleg; Guijas, Carlos; Palermo, Amelia; Palacio-Escat, Nicolàs; Domingo-Almenara, Xavier; Montenegro-Burke, Rafael; Sáez Rodríguez, Julio; Staruschenko, Alexander; Siuzdak, Gary (Science signaling, 2019)
Metabolic changes under pressure: Chronic hypertension causes irreversible damage to the kidneys. Rinschen et al. performed multi-omics analyses of kidney tissue from rats that spontaneously develop hypertension on a high-salt diet. Their metabolomic analysis revealed that at early disease stages, kidney glomeruli showed various metabolic changes, such as increased lipid breakdown, depletion of branched-chain amino acids, and energy stress. Phosphoproteomic analysis uncovered the activation of the kinase AMPK and the inhibition of the kinase-containing complex mTORC1, as would be expected due to energy stress and depletion of the branched-chain amino acid leucine, respectively. Proteomic analysis demonstrated alterations in the abundance of metabolic enzymes, which correlated with the metabolic changes seen at early disease stages. These results suggest that metabolic interventions could be potentially useful in treating hypertension-induced kidney disease. Hypertension is a persistent epidemic across the developed world that is closely associated with kidney disease. Here, we applied a metabolomic, phosphoproteomic, and proteomic strategy to analyze the effect of hypertensive insults on kidneys. Our data revealed the metabolic aspects of hypertension-induced glomerular sclerosis, including lipid breakdown at early disease stages and activation of anaplerotic pathways to regenerate energy equivalents to counter stress. For example, branched-chain amino acids and proline, required for collagen synthesis, were depleted in glomeruli at early time points. Furthermore, indicators of metabolic stress were reflected by low amounts of ATP and NADH and an increased abundance of oxidized lipids derived from lipid breakdown. These processes were specific to kidney glomeruli where metabolic signaling occurred through mTOR and AMPK signaling. Quantitative phosphoproteomics combined with computational modeling suggested that these processes controlled key molecules in glomeruli and specifically podocytes, including cytoskeletal components and GTP-binding proteins, which would be expected to compete for decreasing amounts of GTP at early time points. As a result, glomeruli showed increased expression of metabolic enzymes of central carbon metabolism, amino acid degradation, and lipid oxidation, findings observed in previously published studies from other disease models and patients with glomerular damage. Overall, multilayered omics provides an overview of hypertensive kidney damage and suggests that metabolic or dietary interventions could prevent and treat glomerular disease and hypertension-induced nephropathy. Multi-omics analyses reveal that metabolic changes occur early in hypertension-induced kidney disease.
Gesehen am 25.02.2020